Nutrition competencies for undergraduate medical education: results of an international interdisciplinary consensus (2021)
Background The gap between the nutrition education provided to medical students and the nutrition competencies and attitudes needed for physicians to provide adequate nutrition care is a global concern. There is no universally accepted benchmark on nutrition competencies for doctors. The objective of this study was to establish, by expert consensus, the objectives of undergraduate nutrition medial education, the nutrition core competencies, and strategies for curriculum development in medical nutrition education. Methods We administered a Delphi survey to systematically gather the opinion of a panel of Latin American experts in nutrition. The survey questionnaire was constructed considering scientific literature by using a 5-point Likert scale. Consensus was defined as >70% agreement on the importance of an item (Likert scale 4 and 5). Results A four-round Delphi survey was conducted for this research. In the second, third, and fourth rounds, we validated a total of 130 competencies by consensus, which were distributed into four different thematic areas: (1) basic nutrition concepts, (2) public nutrition and nutrition prevention throughout the life cycle, (3) nutrition status and disease, and (4) nutrition care process. Conclusion The curricula for general physician education in medical school must include health promotion, prevention, and treatment of diseases related to nutrition. This goal can be reached by integrating ≤130 competencies into four different fundamental areas.